+HOXA10-AS Promotes Malignant Phenotypes of Gastric Cancer via Upregulating HOXA10. (16th February 2022) - Cao, Fengyu; Zheng, Yongbin; Yang, Chao; Huang, Suoyang; He, Xiaobo; Tong, Shilun
Abstract : Objective . To study the role of long noncoding RNA HOXA10-AS in gastric cancer (GC) and its underlying mechanism which is one of the most common and fetal malignancies. Long noncoding RNA HOXA10-AS is highly expressed and acts in an oncogenic role in cancers. However, its roles in GC are still unknown. Methods . The expression of HOXA10-AS and HOXA10 in GC tissues from the TCGA database was analyzed. Western blot and qRT-PCR assays were applied to examine the expression of HOXA10-AS and HOXA10. Cell proliferation was evaluated with CCK-8 and EdU incorporation assays. Cell apoptosis was analyzed by flow cytometry. Migratory and invasive capacities were evaluated with wound healing and transwell assays. Results . HOXA10-AS and HOXA10 were upregulated in GC, and their expressions were positively correlated. Knockdown of HOXA10-AS inhibited HOXA10 expression in GC cells. Furthermore, knockdown of HOXA10-AS restrained GC cell proliferation, migration, and invasion but promoted apoptosis. In addition, overexpression of HOXA10-AS promoted malignant phenotypes of GC cells, but all these effects could be reversed by knockdown of HOXA10. Conclusion . HOXA10-AS promoted GC cell proliferation, migration and invasion and enhanced apoptosis via upregulating HOXA10. Our study implies a novel regulatory mechanism of malignant phenotypes and provides potential therapeutic targets for GC.